Encouraging Landscape Water-Conservation Behaviors #4: Florida Homeowners’ Reactions to Messages that Encourage Landscape Water Conservation Practice Adoption - Joy Rumble; Laura A. Warner; Courtney Owens; Alexa Lamm; Randall Cantrell (EDIS)
This is the fourth publication in the Encouraging Landscape Water Conservation Behaviors series, which focuses on improving and encouraging water conservation among Florida residents who use irrigation in their home landscape. This 4-page fact sheet examines the impact of differently framed messages on Florida residents’ attitudes toward good irrigation practices and their perceived ability to implement those practices. Written by Joy Rumble, Laura A. Warner, Courtney Owens, Alexa Lamm, and Randall Cantrell, and published by the Department of Agricultural Education and Communication, June 2016.